Systematics of Podocoma Cass. (Asteraceae: Astereae): a generic reassessment - Sancho, Gisela (2010)
Podocoma is a southern South American genus. Species of Podocoma are herbs with short-radiate capitula, and marginal florets arranged in two or three series. The marginal corollas of Podocoma are shortly rayed with narrow limbs, and its pappus is of two or three series of scabrid bristles. The rostrate cypsela of Podocoma is one of the most distinct features of the genus. Podocoma is a key taxon in understanding the subtribe Podocominae, which includes many of the endemic southern South American genera of the Astereae. Podocoma traditionally contained seven mainly Brazilian species (P. asperrima, P. bellidifolia, P. blanchetiana, P. hieracifolia, P. hirsuta, P. regnelli, P. spegazzini) and the addition of two species of Conyza (C. notobellidiastrum and C. rivularis) was, perhaps, the most important change in the generic concept of Podocoma lately. However, recent molecular and morphology-based phylogenies do not support the inclusion of these two species within Podocoma. Morphological and anatomical studies are herein carried out in order to clarify the taxonomy of Podocoma and to establish the limits of the genus and its species. Based on the results of these morphological and anatomical studies and those from molecular and morphology-based phylogenies we exclude P. notobellidiastrum and P. rivularis from Podocoma. Moreover, P. regnelli and P. asperrima are regarded under synonymy of P. hirsuta and P. spegazzini respectively. Three species, P. bellidifolia, P. blanchetiana, and P. hieracifolia, are recognized herein as a complex, each of them very closely related to the others from a morphological point of view, however, they treated independently.